Paradise under the Field House Lights: When Rituals and Spectacles Suppress Female Students’ Agency - Carolyn Fortuna (Networks: An Online Journal for Teacher Research, 2011)
I am a teacher-researcher. Like many teachers, I design lesson plans, implement constructivist learning events in the classroom, and grade projects and papers. But I am also a qualitative researcher. I decided to remain in the classroom after obtaining my Ph. D. in education so that I could impact students in ways that I feel are beyond the reach of an administrator. My most important data collection device has always been my low-tech teacher journal. A teacher journal allows me to create an account of classroom life where dialogic discourse, offhand remarks, lesson outlines, administrative sessions, and student social conversations become a permanent, written record. I am interested in the ways that my students and the students in the high school in which I teach react to the cultural contexts of their learning and lives.